2017
DOI: 10.1525/elementa.223
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mesoscale variability of modelled sea-ice primary production in the northern Baltic Sea

Abstract: We describe a new ocean-sea ice-biogeochemical model, apply it to the Bothnian Bay in the northern Baltic Sea for the time period 1991-2007 and provide the first long-term mesoscale estimates of modelled sea-ice primary production in the northern Baltic Sea. After comparing the available physical and biogeochemical observations within the study area and the time period investigated with the model results, we show the modelled spatial, intra-and interannual variability in sea-ice physical and biogeochemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…They showed that shorter ice season corresponded to shorter bloom duration with lower peak bloom concentrations and suggested that even though ice algal communities experienced optimal growth conditions (light, space, and nutrients), they did not have enough time to reach high bloom concentrations under the early melt condition. Two modeling studies that compared ice algal production from early and late ice melt years (Tedesco et al, ; this study) support the findings of the idealized sensitivity analysis in Tedesco and Vichi ().…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…They showed that shorter ice season corresponded to shorter bloom duration with lower peak bloom concentrations and suggested that even though ice algal communities experienced optimal growth conditions (light, space, and nutrients), they did not have enough time to reach high bloom concentrations under the early melt condition. Two modeling studies that compared ice algal production from early and late ice melt years (Tedesco et al, ; this study) support the findings of the idealized sensitivity analysis in Tedesco and Vichi ().…”
Section: Discussionsupporting
confidence: 79%
“…In addition to controlling bloom onset and growth rates of the spring ice algal bloom, snow and, to a lesser extent, sea ice thickness, in concert with atmospheric conditions (e.g., air temperatures and wind conditions), impact the timing of ice melt, the loss of the productive bottom layer of ice algae from the sea ice and thus the decline of the ice algal bloom from its peak concentration (Lavoie et al, ; Pogson et al, ; Tedesco & Vichi, ; this study). Our results and others (Haecky & Andersson, ; Duarte et al, ; Tedesco et al, ) suggest that ice algal blooms peak and persist in the presence of some basal melting, depending on the definition of a “bloom period.” Using our threshold value of 5 mg C m −2 to define a bloom, sensitivity analyses showed that productive bottom ice layers disappeared approximately a week to a month earlier under thin snow than under thick snow, regardless of ice thickness. While depth‐integrated biomass sharply decreased during this period of bottom melt, values remained above the bloom threshold until ice retreat.…”
Section: Discussionsupporting
confidence: 64%
“…However, the primary production data we use have not been filtered and should contain the production of both POC and DOC, making the good agreement between the modeled POC production and observed production intriguing. Tedesco et al (2017) obtained similar results with BFM when modeling sea-ice primary production in the Bothnian Bay. Their modeled production of POC agreed well with the total organic carbon production, measured with the same method as the primary production data used in this study.…”
Section: Missing Link In the Carbon Cyclesupporting
confidence: 60%
“…Their modeled production of POC agreed well with the total organic carbon production, measured with the same method as the primary production data used in this study. In the inter-calibration study from the Baltic Sea, where different 14 C methods were compared (Andreasson et al, 2009), it was shown that the method used to measure the TOC production rates, which are used in this study and in Tedesco et al (2017), produced similar, or even lower primary production rates, compared to another method measuring POC production rates. No clear explanation for this inconsistency was given, and it was suggested that more investigations in this matter is needed.…”
Section: Missing Link In the Carbon Cyclementioning
confidence: 72%
See 1 more Smart Citation